A Survey Paper of Study about Data Mining - Upadhyay, Shruti; Patel, Neha; Patel, Rakesh; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Data mining is a process which finds useful patterns from large amount of data The process of extracting previously unknown, comprehensible and actionable information from large databases and using it to make crucial business decisions - Simoudis 1996 This data mining definition has business flavor and for business environments. However, data mining is a process that can be applied to any type of data ranging from weather forecasting, electric load prediction, product design, etc. Data mining also can be defined as the computer-aid process that digs and analyzes enormous sets of data and then extracting the knowledge or information out of it. By its simplest definition, data mining automates the detections of relevant patterns in database.